Mathematics for economists - Simon, Carl P.; Blume, Lawrence (New York : W. W. Norton, 1994)
Introduction. Linear algebra. Calculus of several variables. Optimization. Eigenvalues and dynamics. Advanced linear algebra. Appendices.
Keywords: Mathematics; Mathematical economics; Economics, Mathematical